2019
DOI: 10.1111/dom.13839
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐2 mobilizes lipids from the intestine by a systemic nitric oxide‐independent mechanism

Abstract: Aim To test the hypothesis that gut hormone glucagon‐like peptide‐2 (GLP‐2) mobilizes intestinal triglyceride (TG) stores and stimulates chylomicron secretion by a nitric oxide (NO)‐dependent mechanism in humans. Methods In a randomized, single‐blind, cross‐over study, 10 healthy male volunteers ingested a high‐fat formula followed, 7 hours later, by one of three treatments: NO synthase inhibitor L‐NG‐monomethyl arginine acetate (L‐NMMA) + GLP‐2 analogue teduglutide, normal saline + teduglutide, or L‐NMMA + pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Blunting IRF5 expression results in hepatoprotection through early upregulation of anti-apoptotic and immunoregulatory signaling, increasing T Reg differentiation and IL-10 secretion upon hepatocellular stress (79). Recent research is delving into potential non-inflammatory or non-immune signaling efferent from KCs, notably effector molecules such as insulin-like growth factor-binding protein (IGFBP)-7, regulates insulin sensitivity in the context of obesity (80).…”
Section: Liver Macrophages In Metabolic Inflammationmentioning
confidence: 99%
“…Blunting IRF5 expression results in hepatoprotection through early upregulation of anti-apoptotic and immunoregulatory signaling, increasing T Reg differentiation and IL-10 secretion upon hepatocellular stress (79). Recent research is delving into potential non-inflammatory or non-immune signaling efferent from KCs, notably effector molecules such as insulin-like growth factor-binding protein (IGFBP)-7, regulates insulin sensitivity in the context of obesity (80).…”
Section: Liver Macrophages In Metabolic Inflammationmentioning
confidence: 99%
“…GLP-2 has been shown to stimulate mesenteric blood flow in humans (Bremholm et al, 2010(Bremholm et al, , 2011Høyerup et al, 2013) and animals (Guan et al, 2003(Guan et al, , 2006Deniz et al, 2007), which may involve nitric oxide (NO) signaling (Guan et al, 2003;Hsieh et al, 2015). Recently, we have examined lipid mobilization by GLP-2 in healthy humans with or without a NOS inhibitor L-NGmonomethyl arginine acetate (L-NMMA) (Xiao et al, 2019b). GLP-2 administration after 7 h of fat ingestion increased TG in plasma, in triglyceride-rich lipoprotein (TRL), and mostly in CM, and increased blood flow in the superior mesenteric artery.…”
Section: Oral Glucose and Glp-2 As Stimuli Of Intestinal Lipid Mobilimentioning
confidence: 99%
“…Exogenous GLP‐2 is known to increase postprandial plasma TG levels in humans, mice, and hamsters, through enhanced chylomicron secretion 20,30‐31,34,39,40 . The increased lipid absorption in mice given GLP‐2 has been shown to require CD36 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that insulin‐like growth factor‐1 (IGF‐1) and the intestinal epithelial insulin‐like growth factor‐1 receptor (IE‐IGF‐1R) are required for GLP‐2‐induced increases in intestinal growth and proliferation, while the IE‐IGF‐1R has also been shown to be essential for the stimulatory effects of GLP‐2 on barrier function and microvillus length 24‐29 . Furthermore, although nitric oxide mediates the GLP‐2‐induced increase in CM production in hamsters, this does not appear to be the case in humans 30,31 . However, a role for the IE‐IGF‐1R in GLP‐2‐induced fat uptake has not been tested.…”
Section: Introductionmentioning
confidence: 99%